(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses how action is considered the foundation of acting art. An actor performs their skills and fulfills the general purpose and tasks assigned to them directly and indirectly through action. Action is also the main means of stage expression. The main task of acting art and creative methods is to express the internal and external aspects of the character, and through this, the purpose and idea of the work, via purposeful, active, organic movement.